Analysis of Cadmium (Cd) Heavy Metals Using Bioindicator Climbing pearch fish (Anabas testudineus) Derived from Rawa Taliwang Lake, West Sumbawa Regency 2025 - Zarkasy, M. Rozi; Khairuddin, Khairuddin; Yamin, M. (Jurnal Biologi Tropis, 2025)
Fish is one of the aquatic biota that can be used as a bioindicator of river pollution by determining the content of heavy metals in the fish's body. The purpose of this study was to analyze the heavy metal content of cadmium (Cd) from climbing perch fish (Anabas testudineus) derived from Lake Rawa Taliwang, West Sumbawa Regency 2025. This study was conducted from January to March. Sampling was carried out using the purposive sampling method. Samples were taken as many as 2 fish at each station using a gill net. The species of fish taken were climbing pearch fish that were ready to be harvested. Then the samples were analyzed at the NTB Health, Testing and Calibration Laboratory Center. Data analysis was carried out by taking climbing pearch fish meat and then analyzing the heavy metal content in it using the Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) method. The results of the analysis showed that the heavy metal content of cadmium in climbing pearch fish originating from Lake Rawa Taliwang ranged from 0.026 mg/kg (ppm) to 0.035 mg/kg (ppm). These results indicate that the Taliwang swamp lake is polluted by cadmium, but the cadmium content of climbing perch fish is still below the threshold based on the limit set by the Food and Drug Supervisory Agency (BPOM) No. 9 of 2022 concerning the Maximum Limit of Cadmium Heavy Metal Contamination in processed fish, which is 0.30 mg/kg.